Trends of late HIV presentation and advance HIV disease among newly diagnosed HIV cases in Jiangsu, China: A serial cross-sectional study from 2008 to 2020 - Shi, Lingen; Tang, Weiming; Liu, Xiaoyan; Hu, Haiyang; Qiu, Tao; Chen, Yuheng; Xu, Xiaoqin; Chen, Yunting; Zhang, Zhi; Zhou, Ying; Lu, Jing; Fu, Gengfeng (Frontiers in Public Health, 2022)
Background: This study aimed to assess the trends and determine the factors associated with late presentation (LP) and advanced HIV disease (AHD) among newly diagnosed people living with HIV (PLWH) from 2008 to 2020 in Jiangsu, China. Methods: Newly diagnosed PLWH registered in the HIV surveillance system from 2008 to 2020 were included. Multivariable logistic regression models were used to analyze the factors associated with LP and AHD. The LP and AHD trends were assessed using Joint-point analysis. Results: Of 37251 newly diagnosed PLWH identified, 30251(81.2%) patients met the inclusion criteria. Among those, 16,672 (55.1%) were considered LP, and 8,691 (28.7%) had AHD. LP trends steadily increased from 2008 (39.0%) to 2020 (59.4%), but AHD trends decreased visibly from 2016 (32.3%) to 2020 (23.4%). The overall median CD4 trends decreased slowly from 389 cells/mm3 to 305 cells/mm3 between 2008 and 2020. Married patients and those older than 35 years were more likely to be LP and have AHD. Patients infected via heterosexual transmission had a higher risk of being classified as AHD (aOR:1.13, 95%CI:1.06-1.21) than patients infected via homosexual transmission. Patients that were diagnosed at sexually transmitted infections (STIs) clinics (aOR:1.10, 95%CI:1.01-1.20) and in hospitals (aOR:1.69, 95%CI:1.59-1.79) were more likely to be classified as LP compared with patients diagnosed at voluntary counseling and testing (VCT) centers. Similar, patients diagnosed at STIs clinics (aOR:1.23, 95%CI:1.11-1.36) and hospitals (aOR:2.27, 95%CI:2.12-2.43) were more likely to have AHD than patients diagnosed in VCT. Conclusion: Our findings indicate an alarming burden of LP in Jiangsu, suggesting the need for more attention towards HIV diagnosis at early CD4 stages. National HIV control programs must strengthen comprehensive interventions for HIV prevention and promote HIV services. Also, strategies for HIV prevention (PrEP and PEP), testing, and treatment must be extended, especially among the general population.